Comparison of the sense of kinetics and some kinetic forms between males and females of Riyadh children at the age of (5) years - Laiz, Kholoud; Abedulkareem, Noor alhuda (Journal of Physical Education, 2018)
Comparison of the sense of kinetics and some kinetic forms between males and females of Riyadh children at the age of (5) years The importance of research in games kinetic is one of the most important games that lead children to the spontaneity and freedom of movement and exploration, thinking and creativity to discharge their energies through play as well as the basic forms is a cornerstone in the school sports programs and as a basis to develop the skills of various sports activities. The basic movements of the child are not the basis for the development of the motor skills of different sports based on the area of ​​the experience of mobility and diversity, which acquired in the early childhood. Hence the importance of research thinking, compared to the perception of motor sense and some forms of mobility between males and females of Riyadh children aged (5) years. The problem of research: Some kindergartens have become places for children in the absence of their mothers and their preoccupation with their work. Riyadh does not encourage children to develop thinking and creativity with the movement and to play kinetic games and did not care about their development. long time. Therefore, the researcher decided to perform in the sense of kinetics and some kinetic forms between males and females of the children of Riyadh at the age of (5) years The aim of the research is to identify the sense of kinetics and some kinetic forms between males and females of Riyadh children at the age of (5) years. As well as to identify differences in the perception of motor sense and some forms of mobility between males and females of Riyadh children aged (5) years. The hypotheses assumed by the researcher that there are differences of statistical significance in the sense of mobility between males and females of Riyadh children aged (5) years. There are differences of statistical significance in some forms of mobility between males and females of Riyadh children age (5) years. The researcher reached some conclusions, the most important of which are: There were no significant differences between males and females of Riyadh children at the age of 5 years in the sense of movement (Dayton). There are significant differences between males and females of Riyadh children aged 5 years in some forms of mobility (jogging, jumping, throwing, receiving) The researcher reached some recommendations: The need to pay attention to the motor education lesson in kindergartens and to work on diversifying the games and educational curricula in which they are used. The need for studies similar to other capacities and different ages for other kindergartens.